Cation transport functions in vitro in patients with untreated essential hypertension: a comparison of erythrocytes and leucocytes. - Boon, N; Harper, C; Aronson, J; Grahame-Smith, D (1985)
We have measured intracellular sodium concentrations and specific 3H-labelled glycoside binding characteristics in the erythrocytes and leucocytes of patients with untreated essential hypertension, and have compared the results with those in well-matched normotensive control subjects. Intracellular sodium concentrations were increased in the leucocytes, but not in the erythrocytes, of patients with untreated essential hypertension. There were no differences in the 3H-labelled glycoside binding characteristics of either the erythrocytes or the leucocytes of hypertensive and normotensive subjects. There was no difference in the ability of plasma samples from hypertensive and normotensive subjects to inhibit the binding of [3H]-ouabain to intact leucocytes from normotensive subjects. These findings are not consistent with the presence of increased concentrations of a substance which behaves like a cardiac glycoside in the circulation of patients with untreated essential hypertension.